Efektivitas Layanan Informasi untuk Meningkatkan Pemahaman Perencanaan Karir - Indah Berkat Tini Gea; Mondang Munthe; Justin Foera-era Lase; Elizama Zebua (Journal on Education, 2024)
Career information services can increase students' understanding of career planning. The aim of this research is to reveal the effectiveness of career information services in increasing students' understanding of career planning, using experimental quantitative research methods with a pre-experimental design with one group pretest-posttest design. Data is collected by tests and analyzed quantitatively and the results are described. The research population was all 311 class XI students of SMA Negeri 1 Gido and the sample was drawn by purposive sampling from a class from one class XI -1 study group there were 36 people. The results of the research concluded that of the 36 students before being given treatment, there were 4 people (11.11%) who still had not decided on their career or had no understanding. 26 students (72.22%) had a medium level of understanding, which means they were still unsure about understanding career planning, and there were 6 students (16.67%) who were classified as good at understanding career planning. Meanwhile, after being given treatment, namely being given career information services, there were 33 people (91.7%) who were in the high category in career understanding and 3 people (8.3%) had medium scores. This proves that career information services are very effective in increasing students' understanding of career planning. This is proven by the service results obtained on average of 22,583 with an N-Gain test result of 0.96 which has had a good impact. It is recommended for school counselors to provide career information services to each student to increase their understanding of career planning and also for students to receive this service to increase their understanding of career planning.